Pengaruh Viral Marketing, Celebrity Endorser, dan Brand Image terhadap Keputusan Pembelian Produk Pixy - Natalia, Erika; Transistari, Ralina; Lazuardy, Ilman Taufiq (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
This research aims to analyze the influence of Viral Marketing, Celebrity Endorser and Brand Image on Pixy Product Purchase Decisions. The type of research used in this research is quantitative research, with survey techniques using questionnaires. The sample in this research was Indonesian female consumers, aged at least 17 years, who had purchased Pixy products at least once, with a total sample of 150 respondents. The sampling technique in this research is Non Probability Sampling with the Purposive Sampling method. The data analysis technique uses multiple linear regression analysis. The results of this research show that the Viral Marketing variable does not have effect on purchasing decisions for Pixy products. The Celebrity Endorser variable has a positive effect on Pixy product purchasing decisions, and the Brand Image variable has a positive effect on Pixy product purchasing decisions.